The Prince of Wales visits Guelph, 1919: The Debut of Prince Charming, Celebrity Ladies’ Man - Shelley, Cameron (Ontario History)

(untitled) (The Ontario Historical Society, 2022)
On 21 October 1919, the Prince of Wales and future King Edward VIII visited Guelph, Ontario. The visit was a part of his tour of the Dominion to thank the country for its contributions to the Great War and re-assert the imperial order that the war had so badly shaken. The visit was mundane in most respects except for the Prince’s visit to the Macdonald Institute, a school dedicated to teaching home economics to the nation’s young women. There, the Prince had a unique opportunity to put on his debut appearance as an eligible, young bachelor before the admiring gazes of the dazzled girls of the Institute. In this respect, the stop in Guelph was a signal success for the Prince’s own mission to distinguish himself from his father and to enhance his celebrity as “Prince Charming” to the impressionable young women of the Empire.